A Retrospective Cohort Study of Effects of Antihypertensive and Anticholinergic Medications on Outcomes Following Elective Posterior Lumbar Spine Surgery. Issue 5 (June 2021) - Golubovsky, Joshua L.; Karnuta, Jaret M.; Lee, Maxwell; Enders, Jacob; Banerjee, Aditya; Grits, Daniel; Nowacki, Amy; Ilyas, Haariss; Steinmetz, Michael P.
Abstract : Study Design: This was a retrospective consecutive cohort analysis. Objective: This study aimed to examine the association between commonly prescribed medications and outcomes following posterior lumbar spine surgery. Summary of Background Data: Postoperative complications and prolonged length of stay significantly increase costs following posterior lumbar spine surgery and worsen patient outcomes. To control costs and complications, providers should focus on modifiable risk factors, such as preoperative medications. Antihypertensive and anticholinergic drugs are among the most commonly prescribed medications but can carry significant risks in the perioperative period. Materials and Methods: This study was a retrospective cohort analysis of patients undergoing posterior lumbar spine surgery from January 2014 through December 2015 at a large tertiary care center. The variable selection followed by multivariable logistic and negative binomial regressions were performed. An α threshold of 0.0056 was used for significance after correction for multiple comparisons. A secondary analysis was performed to evaluate confounding or effect modifying variables. Results: This study included 1577 patients. Postoperative urinary retention risk was increased in patients taking loop diuretics. Acute kidney injury risk was increased for patients on nondihydropyridine calcium-channel blockers. Surgical site infection risk was increased for patients on aldosterone receptor blockers. Urinary tract infection risk was increased for patients on anticholinergics for urinary incontinence. Length of stay was decreased for patients on angiotensin II antagonists and angiotensin-converting enzyme inhibitors. Conclusion: A care path should be established in the perioperative period for patients who are deemed to be at higher risk due to medication status to either modify medications or improve postoperative monitoring. Level of Evidence: Level III. Abstract : Supplemental Digital Content is available in the text.